REJUVENATION OF MSME ORGANIZATION WORKFORCE IN MAXIMIZING DIGITAL MARKETING OPERATIONS - Muhamad Fahrezi; Arjuna Rizaldi (Faculty of Economics and Business, Universitas Klabat, 2023)
The rapid growth of information and communication technology in the era of the industrial revolution 4.0 has resulted in many changes in the business sector, one of which is in the field of marketing. However, there are still many MSMEs who have not been able to promote their products digitally, their marketing is still narrow which makes them less competitive than their competitors. The purpose of this research is to explore how to maximize digital marketing. The research method used is qualitative research with the acquisition of secondary data from the results of literature studies obtained from various sources, namely scientific journals, books, and websites. The results of the study found that unqualified human resources hindered MSME actors in utilizing technological growth, the impact on company operations in obtaining maximum profits could not be realized. Rejuvenation of business organizations is one way to solve the problems of MSMEs in operating digital marketing and the problem of youth unemployment in Indonesia. Keywords: Digital Marketing, Human Resources, MSME, Technology Growth, Unemployment Pesatnya pertumbuhan teknologi informasi dan komunikasi di era revolusi industri 4.0 mengakibatkan banyaknya perubahan dalam bidang bisnis, salah satunya pada bidang pemasaran. Namun, masih banyak pelaku UMKM yang belum dapat mempromosikan produknya secara digital, pemasaran yang dilakukan masih bersifat sempit yang membuat mereka kalah saing dengan kompetitor. Tujuan dari penelitian ini adalah untuk menggali cara memaksimalan digital marketing. Metode penelitian yang dilakukan adalah penelitian kualitatif dengan perolehan data sekunder dari hasil studi pustaka yang diperoleh dari berbagai sumber yaitu Jurnal ilmiah, Buku, dan website. Hasil penelitian didapat bahwa SDM yang tidak berkualitas menghambat pelaku UMKM dalam pemanfaatan pertumbuhan teknologi, dampaknya pengoprasian perusahaan dalam mendapatkan laba maksimal tidak dapat direalisasikan. Peremajaan organisasi usaha merupakan salah satu cara yang dapat menyelesaikan permasalahan pelaku UMKM dalam pengoprasian digital marketing dan permasalahan pengangguran usia muda di Indonesia. Kata kunci: Digital Marketing, Pengangguran, Pertumbuhan Teknologi, Sumber Daya Manusia, UMKM.